Antimicrobial, Antioxidant, and Cytotoxic Activities of Juglans regia L. Pellicle Extract - Floriana D'Angeli; Giuseppe Antonio Malfa; Adriana Garozzo; Giovanni Li Volti; Carlo Genovese; Aldo Stivala; Daria Nicolosi; Francesco Attanasio; Francesco Bellia; Simone Ronsisvalle; Rosaria Acquaviva (MDPI AG, 2021)
The difficulty to treat resistant strains-related hospital-acquired infections (HAIs) promoted the study of phytoextracts, known sources of bioactive molecules. Accordingly, in the present study, the pharmacological activities of Juglans regia (L.) pellicle extract (WPE) were investigated. The antiviral effect was tested against Herpes simplex virus type 1 and 2, Poliovirus 1, Adenovirus 2, Echovirus 9, Coxsackievirus B1 through the plaque reduction assay. The antibacterial and antifungal activities were evaluated against medically important strains, by the microdilution method. DPPH and superoxide dismutase (SOD)s-like activity assays were used to determine the antioxidant effect. Besides, the extract was screened for cytotoxicity on Caco-2, MCF-7, and HFF1 cell lines by the 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT) assay. The total phenolic and flavonoid contents were also evaluated. Interestingly, WPE inhibited Herpes simplex viruses (HSVs) replication, bacterial and fungal growth. WPE showed free radical scavenging capacity and inhibited superoxide anion formation in a dose-dependent manner. These effects could be attributed to the high content of phenols and flavonoids, which were 0.377 ± 0.01 mg GE/g and 0.292 ± 0.08 mg CE/g, respectively. Moreover, WPE was able to reduce Caco-2 cell viability, at both 48 h and 72 h. The promising results encourage further studies aimed to better elucidate the role of WPE in the prevention of human infectious diseases.